"The obligation of a promise" as a problem of double contingency: David Hume's ground‐breaking investigation into basic forms of social coordination. (9th January 2022) - Büscher, Christian
Abstract: David Hume's work on "the obligation of promises" is the precursor of many ideas in contemporary sociology. Hume's analysis provides insight into problems of basic social coordination, which in modern theories are characterized as a problem of double contingency . His work has also paved the way for theories of social mechanisms such as trust and of operational principles such as self‐reference . In his writings about the inner workings of promises, Hume even lays the foundation for ideas concerning structure building via communication and the emergence of social systems. In his time, this kind of thinking must have been bold—arguing, for example, against religious beliefs or social contracts as constituting binding motives. In our time, Hume's work is astonishing in how nuanced he already exposed social problems that have to be solved continuously, from moment‐to‐moment, in every social situation anew. Hume's thinking paves the way for later system thinking, especially regarding the ways we can think about the "beginning" of social systems.